MP05: Diagnostic accuracy of point of care ultrasound in undifferentiated hypotension presenting to the emergency department: a systematic review. (May 2019) - Richardson, L.; Loubani, O.; Atkinson, P.
Abstract : Introduction : Undifferentiated hypotension remains one of the most life-threatening presentations to emergency departments (ED) around the world. An accurate and rapid initial assessment is essential, as shock carries a high mortality with multiple unique etiologies and management plans. Point of care ultrasound (PoCUS) has emerged as a promising tool to improve these diagnostic and management challenges, yet its reliability in this setting remains unclear.Methods : We performed a systematic review of Medline, EMBASE, CINAHL, Cochrane, and clinicaltrials.gov databases from inception to June 8, 2018. Databases were reviewed by two independent researchers and all languages were included. The methodological quality of included studies were evaluated using the Quality Assessment of Diagnostic Accuracy Studies (QUADAS-2) tool. Our primary outcome was diagnostic accuracy of PoCUS in hypotension, with secondary outcomes including patient outcomes and changes to management.Results : Our literature search revealed 5345 articles after duplicates were removed, leaving 235 articles for full article review. Following full article review, 9 studies remained and were included in the systematic review. There were 2 randomized control trials, 6 prospective cohort trials, and 1 retrospective cohort trial. For our primary outcome of diagnostic accuracy, eight studies were included; we extracted Kappa values ranging from 0.70 to 0.971, pooled sensitivity ranging from 69% to 88%, and pooled specificity ranging from 88% to 96%. Four studies reported on management change including results reporting shorter time to disposition, change in diagnostic test ordering (18% to 31%), change in consultation (13.6%), change in admission location (12%) and change in management plan (25% to 40%). Only one study reported on patient outcomes, which revealed no survival or length of stay benefit.Conclusion : When assessing for the diagnostic accuracy of PoCUS in the setting of undifferentiated hypotension presenting to the emergency department, we found fair consistency between PoCUS and final diagnosis with high Kappa values, fair to good pooled sensitivities, and good to excellent specificities. There was no strong evidence indicating improved outcomes. However, the large amount of heterogeneity amongst studies has limited our ability to make a strong conclusion except that future research should focus on a uniform study design and patient focused outcomes.